Nanoparticle tension probes patterned at the nanoscale: impact of integrin clustering on force transmission - Liu, Yang; Medda, Rebecca; Liu, Zheng; Galior, Kornelia; Yehl, Kevin; Spatz, Joachim P.; Cavalcanti-Adam, Elisabetta A.; Salaita, Khalid (Nano letters, 2014)
Herein we aimed to understand how nanoscale clustering of RGD ligands alters the mechano-regulation of their integrin receptors. We combined molecular tension fluorescence microscopy with block copolymer micelle nanolithography to fabricate substrates with arrays of precisely spaced probes that can generate a 10-fold fluorescence response to pN-forces. We found that the mechanism of sensing ligand spacing is force-mediated. This strategy is broadly applicable to investigating receptor clustering and its role in mechanotransduction pathways.